High-risk bladder cancer: improving outcomes with perioperative chemotherapy - Daniel Y.C. Heng; Jorge A. Garcia (Frontiers Media S.A., 2011)
Despite treatment with radical cystectomy and pelvic lymph node dissection, muscle invasive bladder cancer has a relapse rate of 50%. Patients can develop regionally advanced or metastatic disease that ultimately leads to death. The addition of neoadjuvant or adjuvant chemotherapy to reduce the risk of relapse and death has been extensively studied over the past two decades. Two contemporary trials coupled with a recent meta-analysis evaluating neoadjuvant chemotherapy demonstrated a modest but real improvement in overall survival. This has made neoadjuvant chemotherapy a standard of care. Clinical trials evaluating adjuvant chemotherapy in patients with high-risk disease have been plagued with statistical flaws and have, therefore, been unable to define the survival impact of this approach. It is hoped that ongoing adjuvant trials that are powered to detect small but meaningful clinical differences will clarify the benefit of chemotherapy after cystectomy. Since there are theoretical advantages and disadvantages to each of these approaches, both are widely used in North America. The evidence behind each approach and potential future developments in this field will be described.